Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I was self studying integral. I meet a difficult problem here: $$\int_{0}^{\infty }{{{x}^{n}}\frac{\sinh ax}{\cosh bx}}\text{d}x=\frac{\pi }{2b}\cdot \frac{{{\text{d}}^{n}}}{\text{d}{{a}^{n}}}\tan \left( \frac{a\pi }{2b} \right)\ \ \ \ \ \left| a \right|<b$$ Anyone know how to deal with it?

share|improve this question

1 Answer 1

up vote 7 down vote accepted

$$\dfrac{\sinh(ax)}{\cosh(bx)} = \dfrac{e^{ax} - e^{-ax}}{e^{bx} + e^{-bx}} = \dfrac{e^{(a-b)x} - e^{-(a+b)x}}{1 + e^{-2bx}} = \left(e^{(a-b)x} - e^{-(a+b)x}\right) \left(\sum_{k=0}^{\infty} (-1)^k e^{-2kbx} \right)$$ This simplifies to $$\sum_{k=0}^{\infty} (-1)^k \left(e^{(a-2kb-b)x} - e^{-(a+2kb+b)x}\right)$$ Hence, \begin{align} I & = \int_0^{\infty} x^n \dfrac{\sinh(ax)}{\cosh(bx)} dx = \sum_{k=0}^{\infty}(-1)^k \left(\int_0^{\infty} x^n e^{(a-2kb-b)x}dx - \int_0^{\infty} x^n e^{-(a+2kb+b)x} dx\right)\\ & = \sum_{k=0}^{\infty} (-1)^k \left(\dfrac{\Gamma(n+1)}{(b+2kb-a)^{n+1}} - \dfrac{\Gamma(n+1)}{(a+2kb+b)^{n+1}}\right)\\ & = n! \left(\sum_{k=0}^{\infty} (-1)^k \left(\dfrac1{(b+2kb-a)^{n+1}} - \dfrac1{(a+2kb+b)^{n+1}}\right)\right) \end{align} Now recall that $$\tan(\pi x/2) = \cot(\pi/2-\pi x/2) = \cot(\pi(1-x)/2)$$ Further, we have $$\cot(\pi y) = \dfrac1{\pi} \lim_{N \to \infty}\left(\sum_{k=-N}^N \dfrac1{y+k}\right)$$ Hence, $$\tan(\pi x/2) = \dfrac1{\pi} \lim_{N \to \infty}\left(\sum_{k=-N}^N \dfrac2{1-x+2k}\right)$$ Plugging in $x=a/b$ and taking derivative term by term you should be able to obtain your desired result.

share|improve this answer
    
Wow! Thx so much! Beatiful proof : ) –  Ryan Jan 27 '13 at 10:18

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.